Theoretical guidance and experimental confirmation on catalytic tendency of M-CeO2(M = Zr, Mn, Ru Or Cu) for NH3-SCR of NO - Phornphimon Maitarad (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Herein, we demonstrate that the degrees of catalytic performance of M-CeO 2 -based catalysts (M=Mn, Cu, Ru or Zr) for an ammonia selective catalytic reduction (NH 3 -SCR) of nitric-oxide (NO) can be estimated using three theoretical terms; (i) an oxygen vacancy formation energy of a catalyst, (ii) an adsorption energy of NO and (iii) an adsorption energy of NH3. Those terms predict the trend of the catalytic performance as the order; Mn-CeO 2 > Cu-CeO 2 > Ru-CeO 2 > Zr-CeO 2 > CeO 2 . To verify the theoretical prediction, the catalysts were synthesized and tested their performances on the NH3-SCR of NO reaction. The normalized NO conversion rates at low temperatures (100-200°C) were measured for Mn-CeO 2 , Cu-CeO 2 , Ru-CeO 2 , Zr-CeO 2 and CeO 2 as 2.61-7.46, 1.30-6.82, 0.73-3.02, 0.81-3.31 and 1.55-2.33mol s −1 m −2 , respectively. In addition, a concept of a structure-activity relationship analysis shows a strong relationship between theoretical and experimental results. Consequently, an application of predicting the ca talytic performance of catalysts from theoretical calculations prior the catalyst synthesis is useful in catalyst design and screening that can reduce time and cost.